Diseño de portales para evitar o reducir el corte en rocas (2017)
Restrictions on topography lead to designs of portals that do not necessarily intersect with the axis of the track at a right angle. The lack of appropriate guidelines in the design for portals and a vague understanding of the behavior of the rock mass bring as a consequence the design of very conservative portals (heavy or rigid support), generating in addition complex construction procedures, longer construction times and a greater environmental impact. This article points to a new approach to the design of portals in a biased way, based on a complete understanding of the behavior of the rock mass and its failure mechanisms. The approach is based on 2D numerical models, complemented with 3D models, for the comparison and optimization of portal design methodology.